Hate and Incivilities in Hashtags Against Women Candidates in Chile (2021–2022) - Jara-Reyes, R (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This study is interested in the phenomenon of violence in social networks against women who hold political office in the framework of the Chilean constitutional process (2021–2022). To study this major socio-political phenomenon, we have used the tracking database “Women and Politics”, composed of 2,912,732 Twitter posts mentioning women candidates and collected between July 2021 and September 2022. Based on this data, we analyzed the network of hashtags by electoral list at points in time: all 2021 messages, all 2022 messages and only hate messages published in 2022 (n = 563,223), codified by an automated detection method. The results of the study reveal that hashtags extracted from messages containing hate speech are better understood under the concept of incivilities. These were expressed in a two-phase electoral process: the presidential election and the constitutional plebiscite. The implications and limits of this study are discussed and considered in context in the conclusion. © 2023 by the authors.